Monitoring of gastrointestinal dysfunction by near-infrared spectroscopy in children with sepsis: a prospective study - Yao, De-Zhen; Wang, Li-Jie (Zhongguo dang dai er ke za zhi, 2022)
To investigate the incidence and mortality of gastrointestinal dysfunction in children with sepsis, the application of near-infrared spectroscopy (NIRS) in monitoring mesenteric regional tissue oxygen saturation (rSO ), and the association between rSO and gastrointestinal dysfunction. In this prospective study, 79 children with sepsis in the pediatric intensive care unit (sepsis group) and 40 children who underwent physical examination in the Department of Child Healthcare (healthy control group) from January to December, 2021 were enrolled as subjects. The related medical data were collected, including general information on admission and at discharge, treatment during hospitalization, and laboratory examination results. NIRS was used to measure mesenteric rSO . Clinical characteristics were compared between the patients with and without gastrointestinal dysfunction. For the 79 children with sepsis, the incidence rate of gastrointestinal dysfunction was 49% (39/79), and the mortality rate of the children wit